Routine Repeat Imaging of Pediatric Blunt Solid Organ Injuries Is Not Necessary. Issue 4 (April 2023) - Fletcher, Kelsey L.; Meagher, Mitchell; Spencer, Brianna L.; Morgan, Madison E.; Safford, Shawn D.; Armen, Scott B.; Hazelton, Joshua P.; Perea, Lindsey L.
Introduction: Nonoperative management of hemodynamically stable patients with blunt splenic and/or hepatic injury has been widely accepted in the pediatric population. However, variability exists in the utilization and timing of repeat imaging to assess for delayed complications during index hospitalization. Recent level-IV evidence suggests that repeat imaging in children should be performed based on a patient's clinical status rather than on a routine basis. The aim of this study is to examine the rate of delayed complications and interventions in pediatric trauma patients with blunt splenic and/or hepatic injuries who undergo repeat imaging prompted either by a clinical change (CC) or non-clinical change (NCC). Methods: A 9-year (2011-2019), retrospective, dual-institution study was performed of children (0-17 years) with blunt splenic and/or hepatic injuries. Patients were grouped based on reason for repeat imaging: CC or NCC. The rate of organ-specific delayed complications and interventions was examined by reason for scan. Results: A total of 307 injuries were included in the study period (174 splenic, 113 hepatic, and 20 both). Of 194 splenic injuries, 30(15.5%) underwent repeat imaging (CC = 19; NCC = 11). Of 133 hepatic injuries, 27(20.3%) underwent repeat imaging (CC = 21; NCC = 6). There was no difference in the incidence of organ-specific delayed complications between the CC and NCC groups. Of the 4 patients with complications necessitating intervention, only one was identified based on NCC. Conclusions: Our data suggest routine repeat imaging is unnecessary in children with blunt splenic and/or hepatic injuries; therefore, practitioners may rely on a patient's clinical change.